Detection of Local Recurrence in Patients with Head and Neck Squamous Cell Carcinoma Using Voxel-Based Color Maps of Initial and Final Area under the Curve Values Derived from DCE-MRI - Lee, J.Y.; Cheng, K.L.; Lee, J.H.; Choi, Y.J.; Kim, H.W.; Sung, Y.S.; Chung, S.R.; Ryu, K.H.; Chung, M.S.; Kim, S.Y.; Lee, S.-W.; Baek, J.H. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: Early detection of local recurrence is important to increase the chance of cure because local recurrence is the main cause of treatment failure in head and neck squamous cell carcinoma. We evaluated the added value of voxel-based color maps of dynamic contrast-enhanced MR imaging compared with conventional MR imaging alone for detecting local recurrence of head and neck squamous cell carcinoma.MATERIALS AND METHODS: We retrospectively enrolled 63 consecutive patients with head and neck squamous cell carcinoma after definitive treatment and posttreatment surveillance MR imaging studies that demonstrated focal enhancement at the primary site. Three independent readers assessed conventional MR imaging and a pair of color maps of initial and final 90-second time-signal intensity areas under the curve from dynamic contrast-enhanced MR imaging. The sensitivities, specificities, and accuracies of both conventional MR imaging alone and combined interpretation of conventional and dynamic contrast-enhanced MR imaging were assessed using the clinicopathologic diagnosis as the criterion standard. κ statistics were used to evaluate interreader agreement.RESULTS: There were 28 patients with subsequently documented local recurrence and 35 with posttreatment change. Adding dynamic contrast-enhanced MR imaging to conventional MR imaging significantly increased the diagnostic accuracies for detecting local recurrence (48%–54% versus 87%–91%; P < .05), with excellent interreader agreement (κ = 0.8; 95% CI, 0.67–0.92 to κ = 0.81; 95% CI, 0.69–0.93). By all 3 readers, the specificities were also significantly improved by adding dynamic contrast-enhanced MR imaging to conventional MR imaging (22%–43% versus 87%–91%; P < .001) without sacrificing the sensitivities (68%–82% versus 86%–89%; P > .05).CONCLUSIONS: Adding voxel-based color maps of initial and final 90-second time-signal intensity areas under the curve from dynamic contrast-enhanced MR imaging to conventional MR imaging increases the diagnostic accuracy to detect local recurrence in head and neck squamous cell carcinoma by improving the specificity without sacrificing the sensitivity.CIconfidence intervalCEcontrast-enhancedHNSCChead and neck squamous cell carcinomaDCEdynamic contrast-enhancedFAUC90final 90-second time-signal intensity area under the curveIAUC90initial 90-second time-signal intensity area under the curveSIsignal intensityTSItime-signal intensity